2019
DOI: 10.1111/medu.14021
|View full text |Cite
|
Sign up to set email alerts
|

You say it, we say it, but how do we use it? Communities of practice: A critical analysis

Abstract: Objectives As educational theories are increasingly used in medical education research there are concerns over how these theories are used, how well they are presented and what the authors intend. Communities of practice (CoP) is one example of an often‐used theory and conceptual framework. This paper presents a critical analysis of how CoP theory is used in medical education research. Methods A critical literature analysis was undertaken of articles published between 1998 and 2018 in eight internationally rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 43 publications
0
36
0
4
Order By: Relevance
“…They demonstrate that the use of this theory was commonly either misrepresentative or cosmetic and raise the important issue of ‘theory dropping’. Just a couple of decades ago, medical education scholars were making impassioned cries for increased use of theory, but this study suggests that the pendulum may, in some ways, have overswung.…”
mentioning
confidence: 82%
See 3 more Smart Citations
“…They demonstrate that the use of this theory was commonly either misrepresentative or cosmetic and raise the important issue of ‘theory dropping’. Just a couple of decades ago, medical education scholars were making impassioned cries for increased use of theory, but this study suggests that the pendulum may, in some ways, have overswung.…”
mentioning
confidence: 82%
“…In this issue of Medical Education, Bransen et al report on a study in which they interviewed clinical students about their perceptions of learning. 1 The authors demonstrate that students progress through three interrelated shifts during their clerkships in an intricate interplay between self-regulated learning (SRL) and co-regulated learning (CRL). They conclude that: 'workplace learning, including development of SRL, always occurs in interaction with others, and that student SRL always involves engagement in CRL.'…”
Section: The Regulation Of Learning In Clinical Environments: a Commementioning
confidence: 99%
See 2 more Smart Citations
“…It also creates a common discourse through which teaching can be discussed and negotiated and a platform on which research about education can be grounded [10,12,18]. However, some reports have shown that learning theories are still not well articulated in clinical teaching and that educators and clinicians are not formally trained on their application in the clinical context [3,7,9,20,22,23].…”
Section: Advantages Of Learning Theories To the Educational Enterprisementioning
confidence: 99%